Domestic support measures in the context of adaptation and mitigation to climate change - Glauber, Joseph W. (Food and Agriculture Organization of the United Nations, 2018)
Climate Smart Agriculture (CSA) has been promoted as a key approach in addressing the effects of climate change. First launched in 2009, CSA refers to agricultural technologies that are well suited to increase farmer livelihoods in the face of a changing climate by 1) raising agricultural productivity; 2) building resilience of livelihoods and farming systems; and 3) reducing carbon emissions. While government implementation of mitigation and adaptation policies may be an effective means to help address climate change, concerns arise, if CSA policies run counter to international trade disciplines. In particular, CSA policies could come into direct conflict with WTO trade rules, if these policies serve to insulate domestic producers from competition. Thus, they could potentially distort production and trade. This paper examines CSA policies in the context of the WTO agreements, including domestic support disciplines under the WTO Agreement on Agriculture.